Interpretation of Ibn Sina's Metaphysics on Islamic Teology and Islamic Education Axiology for Politeknik Negeri Media Kreatif Studies in Medan - Gunawan Gunawan; Muhammad Adyan Simanjuntak; Amroeni Drajat; Salminawati Salminawati (Universitas Nurul Jadid, 2021)
This paper will elaborate on the use of Ibn Sina’s (Avicenna) metaphysics perspective in helping Politeknik Negeri Media Kreatif Medan students to understand Islamic theology and Islamic education axiology. The qualitative (library research) method will further analyze and dissect Avicenna’s metaphysics concept’s relevance to Islamic education. The writer argues that every idea or science that impacts society would have its methodology and objective to ensure its promulgation throughout the years. To achieve an apprehensible understanding, the writer will aim to explain basic knowledge of the idea of “being” and “intellect’’. Furthermore, Avicenna’s “being” and “active intellect” notion has been famous among philosophers and linked to many philosophical and mystical discussions. Therefore, it can be utilized as an essential foundation in understanding Islamic education. His metaphysics concept can explain complex exposition, as religious knowledge has been socially constructed for centuries. Scrutinizing constructed knowledge would require a concept that has the methodology to illustrate the possibilities of higher thinking—making Avicenna’s metaphysics a suitable concept to give profound comprehensive religious study for the student.